Author Correction: Increased Serum Hyaluronic Acid and Heparan Sulfate in Dengue Fever: Association with Plasma Leakage and Disease Severity (Scientific Reports, (2017), 7, 1, (46191), 10.1038/srep46191) - Tang, Tommy Hing-Cheung (Nature Research, 2022)
10.1038/s41598-021-92487-3